2002
DOI: 10.1097/00000658-200209000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy With or Without Distal Gastrectomy and Extended Retroperitoneal Lymphadenectomy for Periampullary Adenocarcinoma, Part 2

Abstract: Radical (extended) pancreaticoduodenectomy can be performed with similar mortality but some increased morbidity compared to standard pancreaticoduodenectomy. The data to date fail to indicate that a survival benefit is derived from the addition of a distal gastrectomy and retroperitoneal lymphadenectomy to a pylorus-preserving pancreaticoduodenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
488
7
43

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 744 publications
(564 citation statements)
references
References 40 publications
26
488
7
43
Order By: Relevance
“…In addition to our own OPD study arm, we reviewed our LPD study data with data on standard pancreaticoduodenectomy from notable randomized trials on pancreaticoduodenectomy. [11][12][13] The disease profile was comparable with published literature except that the mean age of the patients was younger. The mean tumour diameters in both arms were comparable with those studies.…”
Section: Discussionsupporting
confidence: 77%
“…In addition to our own OPD study arm, we reviewed our LPD study data with data on standard pancreaticoduodenectomy from notable randomized trials on pancreaticoduodenectomy. [11][12][13] The disease profile was comparable with published literature except that the mean age of the patients was younger. The mean tumour diameters in both arms were comparable with those studies.…”
Section: Discussionsupporting
confidence: 77%
“…The authors also noted greater lymph node yields in the extended lymphadenectomy group (27 vs. 16, respectively), but again no difference in overall survival between the two groups. Long-term follow-up verified the lack of difference in overall survival between the two groups [19,20]. Similar outcomes were observed in a separate single-institution study at the Mayo Clinic [21].…”
Section: Extended Lymphadenectomysupporting
confidence: 74%
“…11 The ISGPS consensus was partly based on 4 randomized controlled trials (RCT's) investigating the value of an extended lymphadenectomy, which included various lymph node stations. [38][39][40][41] Prior studies have demonstrated that both preoperative CTimaging and visual inspection cannot reliably determine LNM. 12,26 The accurate determination of (loco) regional LNM by endoscopic ultrasonography (EUS) even seems similar.…”
Section: Discussionmentioning
confidence: 99%